Self Financing Development Driven Transportation System - A., Zulkiple; Riza Atiq , Abdullah; Amiruddin, Ismail (2006)
One of the compulsory elements for developers to obtain the development order from the approving authority is the submission of a traffic impact assessment report. The report should cover the assessment of the transportation system before and after or with and without the development project and proposal to mitigate the impact of the development to the transportation system. At present, developers are allowed to implement the mitigation project on piece meal basis by staggering the construction of the access road, the junction with the main road and the improvement along the main road. However, this practice is not sustainable since the construction works is normally completed only toward the end of the project and the impact of the development has been conserved by the authority and the road users. The situation is still manageable by the authority for a single or isolated development but not for multiple or composite developments that will require a systematic and strategic approach in tackling the traffic impact as experienced by the city halls in Malaysia. Fund to implement the planned transportation system is normally made available by the Federal Government since the transportation image of the cities carry national pride but the case may not hold true for other towns. As an option, this paper will explore on the challenges and opportunities for devising a self financing development driven transportation system through coordinated traffic impact assessment.